Engineering Site Investigation for Foundation Design and Construction in Shale and Sandstone Derived Soils of Okitipupa Area, Southwestern Nigeria - Falowo Olusola Olumuyiwa (Geological Engineering Department Universitas Gadjah Mada, 2021)
Geotechnical and geo-electrical investigations of Okitipupa has been carried out with the major objectives of establishing the subsoil/geology, evaluate the geotechnical properties and recommend appropriate foundation alternatives for building foundation construction. Seven borings were carried out with hand auger at two cone penetration test locations, and representative samples were collected and analyzed in the laboratory in accordance with relevant geotechnical engineering standards. In addition, six vertical electrical soundings (VES) were also conducted using Schlumberger configuration. The result of VES delineates three major geologic sequence comprising the topsoil/caprock, sand surficial aquifer, and sand intermediate aquifer. The topsoil has resistivity range of 242 – 1503 ohm-m and thickness of 3.4 - 20.9 m composed of clay sand and sand. This layer is capable of supporting shallow foundation such as simple spread, raft of reinforced concrete, with recommended allowable bearing pressure of 100 KN/m2 at depths of 1.0 m and 3.2 m in the northern and southern part of the study area respectively. The estimated settlement are less than 50 mm using foundation width of 0.6 m, but could be reduced by almost 50% if the width is greater than or equal to 2 m. The groundwater level is very deep (>10 m) and may not likely threatens the integrity of the foundation structures. The estimated allowable bearing capacity for strip footing (203 – 980 KN/m2), square footing (608 – 2940 KN/m2) within 1.4 m depth is appropriate. The capacity of driven (deep foundation) circular piles of diameters 400mm, 500mm, and 600mm, the recommended pile capacity varies at depth of 5 m (69 – 124 KN), 10 m (225 – 378 KN), and 15 m (470 – 766 KN), while that of bored circular pile ranges from (36 – 75 KN), 10 m (93 – 180 KN), and 15 m (170 – 317 KN).